Si Content Effect On the Performance of the Thin Film Anodes for Rechargeable Lithium Ion Batteries - Polat, Deniz Billur; Eryilmaz, Levent; KeleÅ , Ã zgül (The Electrochemical Society, 2013)
Abstract not Available.